IABS/CEPI platform technology webinar: Is it possible to reduce the vaccine development time?. (June 2021) - Vandeputte, Joris; Saville, Melanie; Cavaleri, Marco; Friede, Martin; Hacker, Adam; Mueller, Stefan O.; Rizzi, Ruben; Smith, Dean; Thirstrup, Steffen; Wagner, Ralf; Baay, Marc; Neels, Pieter
Abstract: The International Alliance for Biological Standardization and the Coalition for Epidemic Preparedness Innovations organized a joint webinar on the use of platform technologies for vaccine development. To tackle new emerging infectious diseases, including SARS-CoV-2, rapid response platforms, using the same basic components as a backbone, yet adaptable for use against different pathogens by inserting new genetic or protein sequences, are essential. Furthermore, it is evident that development of platform technologies needs to continue, due to the emerging variants of SARS-CoV-2. The objective of the meeting was to discuss techniques for platform manufacturing that have been used for COVID-19 vaccine development, with input from regulatory authorities on their experiences with, and expectations of, the platforms. Industry and regulators have been very successful in cooperating, having completed the whole process from development to licensing at an unprecedented speed. However, we should learn from the experiences, to be able to be even faster when a next pandemic of disease X occurs. Highlights: Platform technologies have been essential for rapid vaccine development. A true platform approach seems possible to adapt vaccines to variants. Better understanding of the immune response to components of the platforms is needed. Establishment and adoption of platform principles will require alignment among stakeholders. The nominal target for development and approval of new vaccines should be 100 days.